EXTENDING THE LIFE OF SCANIA P410 ENGINE BY PREVENTING ENGINE OVERHEAT: A CASE STUDY AT PT ABC, TENGGARONG, EAST KALIMANTAN, INDONESIA - NT Iwan Prasetyo Nugroho; rer. nat. Filiana Santoso; Gembong Baskoro (Fakultas Teknik Universitas Islam Makassar, 2026)
Engine overheating is a critical issue that reduces the performance and lifespan of heavy-duty trucks. At PT ABC, Tenggarong, East Kalimantan, Indonesia, the Scania P410 fleet experienced recurring overheating, leading to reduced reliability, increased downtime, and higher maintenance costs. This study applies the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) framework to identify root causes and propose improvements. Data were obtained from operational records, maintenance logs, and field observations. Root cause analysis using Fishbone Diagram and Failure Mode and Effect Analysis (FMEA) revealed inadequate preventive maintenance, inefficient cooling systems, and poor operating practices as the main contributors. Kaizen-based improvements, including enhanced maintenance scheduling, standardized cooling inspections, and operator training, were implemented. As a result, overheating incidents decreased significantly, maintenance costs were reduced, and engine life was extended. The findings confirm that structured problem-solving methods are effective in improving technical reliability in the heavy equipment sector.